Pengembangan Buku Cerita Rakyat Sumbawa: “Lalu Dia Lala Jinis” Dalam Mata Pelajaran Bahasa Indonesia - Sunia Tri Putri; Moh. Irawan Zain; Safruddin (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This research and development was carried out against the background of the reality on the ground that there were no local wisdom-based textbooks, especially Sumbawa folklore, which were in accordance with the competencies to be achieved. In the conditions of people's lives that are experiencing a moral crisis, literature can actually be used as a 'helper' because learning literature besides being able to help students love to read and write, can also be used as a means to improve students' personalities. This study aims to describe the validity of the Sumbawa folklore book model